Pengembangan Video Pembelajaran Matematika Berbasis STEM untuk Meningkatkan Kemampuan Literasi Numerasi - Nisya Fajri; Lia Hamimi; Rismawati; Fara Febria (JNPM (Jurnal Nasional Pendidikan Matematika), 2025)
Students must have good literacy skills because literacy skills are the standard for the nation's progress and mastery of life skills. Numeracy literacy helps students understand the role of mathematics in solving everyday life problems. This research aims to develop STEM-based mathematics learning videos to improve numeracy literacy skills. This research uses the R&D approach to the ADDIE development model. The subjects in the research were material expert validators and multimedia experts as well as 33 class X students. The instruments used are needs analysis sheets, material validation sheets, multimedia validation sheets, acceptance sheets, and test instruments. The research results obtained were the average validation results of content/learning video material of 4.15 in the feasible category, the average validation results of the multimedia learning video construction that was developed was 4.3 in the very feasible category, as well as the average domain validation results. multimedia acceptability was 4.35 in the very high acceptability category, while the effectiveness test obtained a pretest average of 6.67 while the posttest average value was 66.8. The increase in posttest scores compared to the pretest shows that the test using STEM-based learning videos can effectively improve students' literacy and numeracy skills. The application of STEM-based learning videos can also increase students' learning motivation and interest in learning, this can be seen from student activity and interest in studying the videos developed.